Activation of PPARγ by pioglitazone does not attenuate left ventricular hypertrophy following aortic banding in rats - Weiss, Celine; Hagenmüller, Marco; Pichler, Martina; Münz, Sebastian Gregor; Ochs, Marco; Buß, Sebastian Johannes; Bekeredjian, Raffi; Katus, Hugo; Hardt, Stefan (Naunyn-Schmiedeberg's archives of pharmacology, 2010)
Sustained left ventricular hypertrophy (LVH) accelerates cardiac dysfunction and heart failure. Previous reports have suggested that activation of the peroxisome proliferator-activated receptor γ (PPARγ)-dependent pathway is involved in development of cardiac hypertrophy. Thiazolidinediones (TZDs) such as pioglitazone activate PPARγ and are clinically used as antidiabetics. Given inconsistent reports regarding effects of TZDs on LVH, we examined in the present study the influence of pioglitazone on LVH in a rat model of aortic banding...
Gesehen am 19.10.2023